A periodic DFT study on adsorption of small molecules (CH4, CO, H2O, H2S, NH3) on the WO3 (001) surface-supported Au. (21st February 2020) - Lin, Long; Huang, Jingtao; Yu, Weiyang; He, Chaozheng; Tao, Hualong; Xu, Yonghao; Zhu, Linghao; Wang, Pengtao; Zhang, Zhanying
Abstract: Gas molecules (such as CH4, CO, H2 O, H2 S, NH3 ) adsorption on the pure and Au-doped WO3 (001) surface have been studied by Density functional theory calculations with generalized gradient approximation. Based on the the calculation of adsorption energy, we found the most stable adsorption site for gas molecules by comparing the adsorption energies of different gas molecules on the WO3 (001) surface. We have also compared the adsorption energy of five different gas molecules on the WO3 (001) surface, our calculation results show that when the five kinds of gases are adsorbed on the pure WO3 (001) surface, the order of the surface adsorption energy is CO > H2 S > CH4 > H2 O > NH3 . And the results show that NH3 is the most easily adsorbed gas among the other four gases adsorbed on the surface of pure WO3 (001) surface. We also calculated the five different gases on the Au-doped WO3 (001) surface. The order of adsorption energy was found to be different from the previous calculation: CO > CH4 > H2 S > H2 O > NH3 . These results provide a new route for the potential applications of Au-doped WO3 in gas molecules adsorption.